2013
DOI: 10.1016/j.canlet.2013.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling pathway targeted therapy suppresses tumor progression and metastatic spread in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) remains a lethal human malignancy with historically limited success in treatment. The role of aberrant Notch signaling, which requires the constitutive activation of γ-secretase, in the initiation and progression of PDA is well defined and inhibitors of this pathway are currently in clinical trials. Here we investigated the in vivo therapeutic effect of PF-03084014, a selective γ-secretase inhibitor, alone and in combination with gemcitabine in pancreatic cancer xenograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 48 publications
2
95
0
Order By: Relevance
“…This was shown by the studies that overexpression of Notch1 leads to increasing in the formation of pancreatospheres along with expression of the CD44 and EpCAM CSC surface markers. Other studies reported that expression of Oct4, Nanog, and PDX1 in Notch2 positive human pancreatic adenocarcinoma cells [69] . The Oct4, Nanog and PDX1 are also considered as markers of self-renewal of pancreatic CSCs.…”
Section: Signaling Pathways Altered By Cscsmentioning
confidence: 94%
“…This was shown by the studies that overexpression of Notch1 leads to increasing in the formation of pancreatospheres along with expression of the CD44 and EpCAM CSC surface markers. Other studies reported that expression of Oct4, Nanog, and PDX1 in Notch2 positive human pancreatic adenocarcinoma cells [69] . The Oct4, Nanog and PDX1 are also considered as markers of self-renewal of pancreatic CSCs.…”
Section: Signaling Pathways Altered By Cscsmentioning
confidence: 94%
“…PF-03084014 (PF-4014) is a GSI developed by Pfizer, which shows antitumor efficacy in hematologic, breast, colorectal, and pancreatic cancer models (13)(14)(15)(16)(17)(18), and suppresses hepatic metastases of neuroblastoma and breast cancer cells (19). Currently PF-03084014 is in phase I or phase II trials for the treatment of T-ALL, lymphoma, desmoid tumors, and fibromatosis (4,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…However, tumor growth is not sustainable without CSCs to replenish the bulk population and the tumor will eventually degenerate as bulk tumor cells are depleted. Therefore it is of paramount importance to develop targeted therapies, which eliminate CSC, thereby destroying the sole source for new tumor cells (25).…”
Section: Discussionmentioning
confidence: 99%